Inhibitory effects of imatinib mesylate on human epidermal melanocytes. (1st March 2014) - Wang, Y.; Zhao, Y.; Liu, L.; Zhang, L.; Xiao, H.; Wu, K.; Xu, Y.; Hu, Y.; Fu, H.; Cao, W.; Luo, Y.; Huang, H.
Summary: Background: In recent years, increasing attention has been focused on the skin hypopigmentation that develops after the initiation of imatinib mesylate therapy in patients with chronic myeloid leukaemia (CML). Aim: To understand the underlying mechanism of this hypopigmentation effect, and to explore the possibility of using imatinib in the treatment of pigmentation disorders. Methods: We examined the effects of imatinib on the proliferation, apoptosis, melanin content and melanogenic activity of human primary epidermal melanocytes. The responsible molecular events were also investigated in a mechanism study. Results: We found that imatinib led to a dramatic decrease in total melanin content in cultured melanocytes, by affecting melanocyte number and/or melanogenesis in a dose‐dependent manner. This inhibition of melanogenesis was due to suppressed expression of tyrosinase and microphthalmia‐associated transcription factor (MiTF). Furthermore, stem cell factor (SCF)‐stimulated c‐Kit activation and melanocyte proliferation were completely abrogated by imatinib. Conclusions: Inactivation of c‐Kit signalling by imatinib has inhibitory effects on melanocyte survival, proliferation and melanogenesis, which explains the clinical hypopigmentation seen in patients with CML. These results also support using imatinib as a clinical depigmentation agent when dosage being carefully determined.